Platelet Function in Viral Immunity and SARS-CoV-2 Infection - Allaoui, Afaf; Khawaja, Akif A.; Badad, Oussama; Naciri, Mariam; Lordkipanidzé, Marie; Guessous, Fadila; Zaid, Younes (Seminars in Thrombosis and Hemostasis, 2021)
Platelets, as nonnucleated blood components, are classically recognized for their pivotal role in hemostasis. In recent years, however, accumulating evidence points to a nonhemostatic role for platelets, as active participants in the inflammatory and immune responses to microbial organisms in infectious diseases. This stems from the ability of activated platelets to secrete a plethora of immunomodulatory cytokines and chemokines, as well as directly interplaying with viral receptors. While much attention has been given to the role of the cytokine storm in the severity of the coronavirus disease 2019 (COVID-19), less is known about the contribution of platelets to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Here, we give a brief overview on the platelet contribution to antiviral immunity and response during SARS-CoV-2 infection.
Keywords: platelets; hemostasis; inflammation; SARS-CoV-2; COVID-19; viral infections